Isotope effects on energy, particle transport and turbulence in electron cyclotron resonant heating plasma of the Large Helical Device. (18th October 2019) - Tanaka, K.; Ohtani, Y.; Nakata, M.; Warmer, F.; Tsujimura, T.; Takemura, Y.; Kinoshita, T.; Takahashi, H.; Yokoyama, M.; Seki, R.; Igami, H.; Yoshimura, Y.; et al.
Abstract: Positive isotope effects have been found in electron cyclotron resonant heating plasma of the Large Helical Device (LHD). The global energy confinement time ( τ E ) in deuterium (D) plasma is 16% better than in hydrogen (H) plasma for the same line-averaged density and absorption power. The power balance analyses showed a clear reduction in ion energy transport, while electron energy transport does not change dramatically. The global particle confinement time ( τ p ) is degraded in D plasma; τ p in D plasma is 20% worse than in H plasma for the same line-averaged density and absorption power. The difference in the density profile was not due to the neutral or impurity sources, but rather was due to the difference in the transport. Ion scale turbulence levels show isotope effects. The core turbulence ( ρ = 0.5–0.8) level is higher in D plasma than in H plasma in the low collisionality regime and is lower in D plasma than in H plasma. The density gradient and collisionality play a role in the core turbulence level.